Using an interprofessional team to provide refugee healthcare in an academic medical centre - Catherine E Elmore; Jeffrey M Tingen; Kelly Fredgren; Sarah N Dalrymple; Rebekah M Compton; Elizabeth L Carpenter; Claudia W Allen; Fern R Hauck (Family Medicine and Community Health)
Introduction The International Family Medicine Clinic (IFMC) was established in 2002 by the University of Virginia Department of Family Medicine to provide comprehensive, timely, culturally sensitive and high-quality healthcare to the growing refugee and special immigrant population in Central Virginia, USA.Methods The purpose of this paper is to describe the IFMC, with a specific focus on interprofessional roles, interprofessional collaboration, community partnerships and the services and resources available to IFMC patients.Results The clinic has served over 3100 refugees from 60 countries in its 16-year history. In 2019, the clinic staff now includes 4 attending physicians, 2 nurse practitioners and 14 residents who have dedicated clinic time to see refugees; a registered nurse care coordinator and a social worker dedicated to the IFMC refugee population; 2 clinical psychologists and doctoral students in clinical psychology; and a clinical pharmacist. The IFMC also provides onsite psychiatric care. A process flow map depicts the interconnectivity of interprofessional team members working together with other specialty care providers within the medical centre and with community partners on behalf of refugee patients through the resettlement process.Conclusion Individuals who arrive in the USA as refugees are a particularly vulnerable patient group and often require an interprofessional team approach. The IFMC may serve as a model for other institutions interested in starting a similar interprofessional, refugee-centred medical home.